The Effects of Mobile Service Quality and ERecovery Service Quality on E-Satisfaction in Bukalapak Application Users - Taufik Hidayah, Riski; Dzil Fadhli Tauwli, Muhammad; Saefudin, Nugraha (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to find out how much influence the quality of mobile-based services and the recovery of electronic services have on the satisfaction of users of the Bukalapak trading application. The research uses descriptive methods and the method of verification with the population of consumers who have shopped with the Bukalapak buy and sell application, represented by 200 respondents. The analytical method used is Rank Spearman correlation, coefficient of determination, and t test with a significance level of 5% with the use of IBM Statistics 24 SPSS software. The results showed that mobile service quality contributed to the effect of e-satisfaction by 60.84% and recovery service quality contributed 43.03% to e-satisfaction. Some aspects that can be of concern are that companies need to review and pay attention to speed in responding to complaints from consumers and allowance to users of the Bukalapak application as a sign of apology for the inconvenience of malfunctions of the application.